2006
DOI: 10.1590/s1676-06032006000300018
|View full text |Cite
|
Sign up to set email alerts
|

Alometria de Caryocar brasiliense (Caryocaraceae) em diferentes fisionomias do Parque Estadual da Serra de Caldas Novas, GO

Abstract: The relationship between size and shape in trees is important for understanding adaptive differences of species. Variations in these characteristics reflect the environmental conditions they are exposed to, being a response to the particular stress experienced by these individuals. Within this context, the present study aimed to analyze the allometric relation of two populations of Caryocar brasiliense Camb, present in two different physiognomies (cerradão and cerrado stricto sensu) of the Parque Estadual da S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Costa et al (2012) observed that increasing the density of tree vegetation contributed to increase competition of the canopy for light. Siqueira (2006), verified that competition of the crown by light favors the development of the higher branches in detriment of the lower ones. On the other hand, Costa et al (2012) observed that the decrease of the density of the tree vegetation facilitated the penetration of light, making possible the existence of lower live branches.…”
Section: Resultsmentioning
confidence: 77%
“…Costa et al (2012) observed that increasing the density of tree vegetation contributed to increase competition of the canopy for light. Siqueira (2006), verified that competition of the crown by light favors the development of the higher branches in detriment of the lower ones. On the other hand, Costa et al (2012) observed that the decrease of the density of the tree vegetation facilitated the penetration of light, making possible the existence of lower live branches.…”
Section: Resultsmentioning
confidence: 77%
“…The more-than-geometric growth indicates an even faster growth during the juvenile stage within the native range, where the incidence of light under the canopy is lower than within the invaded range. Other studies have also shown changes in the allometry of the same species growing in different vegetation types, such as forests and savannahs (Archibald & Bond 2003;Siqueira 2006). We propose that, in the native range, light is Figure 3 Logarithmic distribution of frequencies for each ontogenetic stage of S. parahyba.…”
Section: Ontogenetic Stages and Allometrymentioning
confidence: 87%
“…Allometric variation between height and diameter usually follows one of three main models: (1) geometric similarity (allometric coefficient = 1), with diameter and height increasing proportionally (King 1990;Niklas 1995;Olesen 2001;Silveira et al 2012), which serves as a null model of tree proportions, thus, not related to any mechanical principle (King 2011); (2) elastic similarity (coefficient = 0.67) where the diameter is just large enough to prevent falling or bending resulting from the individual's weight (McMahon 1973;McMahon & Kronauer 1976); and (3) stress similarity (coefficient = 0.5) where the physical stress resulting from the constant action of wind and weight of the plant (Dean & Long 1986) is evenly distributed along the trunk's height (McMahon & Kronauer 1976). Individual tree species may exhibit different height/trunk allometries in different environments (Archibald & Bond 2003;Weiner 2004;Siqueira 2006;Harja et al 2012), and the ability to be plastic for allometry may be important for the survival and spread of an introduced tree species across different environments, because allometry changes may result in an increase in fitness (Chun et al 2007) and/or in homeostasis (Davidson et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, Abdala et al (1998); Vale et al (2002); Vale and Felfili (2005); Medeiros et al (2008); Crespilho and Schiavini (2009) ;Lima et al (2010);Carvalho (2011);Mews;Marimon and Maracahipes (2011);Paiva et al (2011) and Ribeiro et al (2012) worked with the diameter measured at 0.30 meters from the soil (DAS 1 ). Castro and Kauffman (1998) and Siqueira (2006) used both measurement heights in their work.…”
Section: Introductionmentioning
confidence: 99%